High spin polarization in epitaxial films of ferrimagnetic Mn3Ga - COEY, JOHN; VENKATESAN, MUNUSWAMY; RODE, KARSTEN; STAMENOV, PLAMEN (My University, 2011)
Ferrimagnetic Mn3Ga exhibits a unique combination of low saturation magnetization (Ms=0.11 MA m−1) and high perpendicular anisotropy with a uniaxial anisotropy constant of Ku = 0.89 MJ m−3. Epitaxial c-axis films exhibit spin polarization as high as 58%, measured using point-contact Andreev reflection. These epitaxial films will be able to support thermally stable sub-10-nm bits for spin-transfer torque memories.
PUBLISHED
Keywords: Ferrimagnetic Mn3Ga; Ferrimagnetic Mn3Ga